Development of a methodology for the ecological monitoring of range trends in Kenya - Bille, Jean-Claude; Heemstra, H.H. (International Livestock Centre for Africa, 1978)
Discusses the methodology for ecological monitoring. Reviews the principles for the establishment of a monitoring network. Discusses the application to the Kenyan situation. Presents results of the establishment of monitored sites on two ranches in Taita district. Includes a bibliography on environment, vegetation, range management and fodder crops in Kenya.